2013
DOI: 10.1371/journal.pone.0083992
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Determination of Drug Transfer from Drug-Coated Balloons

Abstract: Drug-coated balloons are medical devices designed to locally deliver drug to diseased segments of the vessel wall. For these dosage forms, drug transfer to the vessel wall needs to be examined in detail, since drug released into the blood is cleared from the site. In order to examine drug transfer, a new in vitro setup was developed combining the estimation of drug loss during advancement to the site of application in a model coronary artery pathway with a hydrogel compartment representing, as a very simplifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Advancement in revascularization procedures performed by vascular surgeons during the last 20 years has played a significant role in management of the most severe form of peripheral artery disease, including critical limb ischemia and tissue necrosis 10 . The addition of hydrophilic polymer coatings to the surfaces of catheters, stents, balloons, guidewires, and other revascularization devices decreases the coefficient of friction, which therefore allows for easier passage and less vessel spasm through narrow vascular spaces 11, 12, 13, 14. Similar devices are used by interventional cardiologists and radiologists, neurosurgeons, and nephrologists in addition to other subspecialists in the revascularization and repair of vessels of the lungs, heart, brain, and kidneys 14, 15, 16, 17.…”
Section: Discussionmentioning
confidence: 99%
“…Advancement in revascularization procedures performed by vascular surgeons during the last 20 years has played a significant role in management of the most severe form of peripheral artery disease, including critical limb ischemia and tissue necrosis 10 . The addition of hydrophilic polymer coatings to the surfaces of catheters, stents, balloons, guidewires, and other revascularization devices decreases the coefficient of friction, which therefore allows for easier passage and less vessel spasm through narrow vascular spaces 11, 12, 13, 14. Similar devices are used by interventional cardiologists and radiologists, neurosurgeons, and nephrologists in addition to other subspecialists in the revascularization and repair of vessels of the lungs, heart, brain, and kidneys 14, 15, 16, 17.…”
Section: Discussionmentioning
confidence: 99%
“…Seidlitz et al used pure PTX-coated balloons and showed PTX transfer rates to gel below 1% (calcium alginate as vessel model). 12 In their study, they also used a model of a coronary artery pathway to investigate drug loss and drug transfer to the gel. However, in our study with the novel DCB coating more PTX was delivered upon dilation (calcium alginate: 6.4 AE 3.8% compared to below 1%).…”
Section: Comparison Of Different Hydrogels In the Ow-through Cellmentioning
confidence: 99%
“…9 To date, there are only a few in vitro studies presented, characterizing and describing the simulated use of drug coated balloon catheters in an in vitro vessel model. [10][11][12] The previously used models are far from physiological properties of the material, e.g. a silicone tube acts like an artery.…”
Section: Introductionmentioning
confidence: 99%
“…The excipient enhances the adhesion of the drug to the balloon surface, increases the stability of the drug coating during handling and delivery, and maximizes drug retention to the targeted arterial segment. [18][19][20][21][22][23][24] Current DCBs excipients include polysorbate and sorbitol, urea, polyethylene glycol (PEG) and butyryl-tri-hexyl citrate (BTHC). The rationale for the selection of these various excipients varies.…”
Section: Introductionmentioning
confidence: 99%